Three Phase Induction Motor: Simulation and Speed Control of Motor Drives Controlling the Applied Voltage: Advancements and Analysis of Speed Control Methods in Induction Motors (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Induction motors are the most widely used electrical motors due to their reliability, low cost and robustness. However, induction motors do not inherently have the capability of variable speed operation. Due to this reason, earlier dc motors were applied in most of the electrical drives. But the recent developments in speed control methods of the induction motor have led to their large scale use in almost all electrical drives. Out of the several methods of speed control of an induction such as pole changing, frequency variation, variable rotor resistance, variable stator voltage, constant Vf control, slip recovery method etc., the closed loop constant Vf speed control method is most widely used. In this method, the Vf ratio is kept constant which in turn maintains the magnetizing flux constant so that the maximum torque remains unchanged. During starting of an induction motor, the stator resistance and the motor inductance (both rotor and stator) must be kept low to reduce the steady state time and also to reduce the jerks during starting. On the other hand, higher value of rotor resistance leads to lesser jerks while having no effect on the steady state time. The vector control analysis of an induction motor allows the decoupled analysis where the torque and the flux components can be independently controlled (just as in dc motor). This makes the analysis easier than the per phase equivalent circuit.